Finance for Engineers - Crundwell, Frank (Springer, 2017)
Engineering solutions and financial decisions are intimately tied together. The best engineers combine the technical and financial cases in determining new solutions to opportunities, challenges and problems. In order to get a project approved, no matter its size, the financials must be clear and compelling. To have an impact on the company’s performance, a practising engineer must learn to argue the business case as part of the technical solution. Finance for Engineers: Evaluation and Funding of Capital Projects provides a framework for engineers and scientists to undertake financial evaluations and assessments of engineering or production projects. The material covered enables the reader to understand how the economics of a technical project affects the finances of the company. The integration of the technical and financial decision-making is demonstrated through case studies and examples relevant to the practising engineer. The book equips engineers and scientists with the tools to contribute positively to the financial and strategic decisions within the organization.